PENINGKATAN PEMAHAMAN TAJWID SISWA KELAS VIII 4 MELALUI STRATEGI COOPERATIF LEARNING DI TPQ SMPN 13 BINTAN - Zulkifli Zulkifli (TANJAK, 2021)
The method has a very significant position in achieving the goals of Islamic education, therefore, the application of the right method greatly influences the success in the teaching and learning process. On the other hand, errors in implementing the method will be fatal. In the tajwid material, student learning outcomes at SMPN 13 Bintan are classified as low. This can be seen from the results of the assessment carried out by the teacher during grade VIII which stated that students who scored below the Minimum Completeness Criteria) were more than 50%. To solve this problem, try to find a solution to improve the learning outcomes of tajwid material by using the "COOPERATIVE LEARNING" technique, which is a learning technique that uses three stages of the process, namely, discussion and group work. The research implementation process was carried out for two cycles. Cycles 1 and 2, each cycle consisting of 2 meetings. Meeting 1 carried out the "Discuss" stage, while meeting 2 conducted the "Group work" stage. The technique of "COOPERATIVE LEARNING" has been proven to improve student learning outcomes of 20.46% mastery of concepts and 13.63% application. 100% of students stated that the technique was. fun and able to make the classroom atmosphere come alive so that students become motivated. "Cooperative Learning" technique also brings positive benefits to students' ability to express learning outcomes through words and critical thinking